2009
DOI: 10.1136/bjo.2009.160713
|View full text |Cite
|
Sign up to set email alerts
|

Optic neuropathy endemic in secondary school children in Dar es Salaam, Tanzania

Abstract: Aim:To investigate the prevalence and causes of optic neuropathy, reported as epidemic in 1997, among secondary school students in Dar es Salaam, Tanzania. Patients and methods:10,892 first year students from 63 secondary schools within 30km from the base hospital were interviewed and had a visual acuity screening test. Students failing the 6/12 -line in either eye were defined as having 'poor eyesight' and referred to the base hospital where an optometrist re-tested visual acuity and refracted them. An ophtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Given their similarity to the Cuban epidemic (7,8), and their shared clinical features with Leber herditary optic neuropathy (14), it seems likely that both the Somalian and Tanzanian optic neuropathies are disorders resulting from mitochondrial dysfunction. This has already been proposed for the Cuban epidemic (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Given their similarity to the Cuban epidemic (7,8), and their shared clinical features with Leber herditary optic neuropathy (14), it seems likely that both the Somalian and Tanzanian optic neuropathies are disorders resulting from mitochondrial dysfunction. This has already been proposed for the Cuban epidemic (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 94%
“…If epidemic optic neuropathy is associated with nutritional deficiencies, the increased demands of pregnancy followed by lactation might also be a contributing factor. With optic neuropathy in Tanzania now classed as endemic (9), and evidence presented here for the first time of its prevalence in Somalia, more effective treatment strategies are required. Current treatment of Bvitamin supplementation based on its use in the Cuban epidemic (7,8) has proven very successful in acute cases in Tanzania (Dalmar et al, unpublished data, 2010), and the large extent of visual loss reported over the first month in Somalia places emphasis on the need for early diagnosis and treatment through Training community eye care workers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] These share some commonalities with a 1991-1993 ON epidemic in Cuba. 8 Such ON is typically characterized by progressive bilateral vision loss (although not necessarily symmetrical), with impaired color perception, visual field scotomata and optic nerve head (ONH) pallor.…”
Section: Introductionmentioning
confidence: 99%
“…First reported in 1988, the most recent epidemic, also occurred in Tanzania, appeared to be endemic within the secondary school population of Dar es Salaam (7). Patients presented with bilateral, simultaneous, usually painless, visual loss over 2-12 weeks and were found to have impaired color vision, central or cecocentral scotomas, and, in many cases, peripheral neuropathy (8)(9)(10).…”
mentioning
confidence: 97%